1999
DOI: 10.1111/j.1574-6968.1999.tb13473.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a new exo-cellulase gene,cel3, inIrpex lacteus

Abstract: A new cellulose-inducible gene (named cel3) was isolated from a strain of the white rot basidiomycete, Irpex lacteus MC-2. The cel3 open reading frame, containing two introns, encodes a polypeptide of 526 amino acids residues with a molecular mass of 55794 Da. Expression of the cel3 gene was induced by various insoluble celluloses and CM-cellulose. Transcription of cel3 was abolished when cells were cultivated in media containing the above cellulosic substrates, but added with glucose, fructose or lactose, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The conversion of cellulose into simple forms of carbon may be useful for the production of bioenergy (Bisaria and Ghose, 1981; Schallmey et al , 2004). In general, the degradation of cellulose occurs by the induction of three types of enzymes: endo-1,4-β-D-glucanase (endocellulase), exo-1,4-β-D-glucanase (exocellulase) and β-glucosidase (cellubiose hydrolase) (Eveleigh, 1981; Hamada et al , 1999). Enzymes called endoglucanases or endocellulases represent a group of cellulases active in the cleavage of random regions within cellulose, producing oligosaccha-rides with variable sizes.…”
Section: Introductionmentioning
confidence: 99%
“…The conversion of cellulose into simple forms of carbon may be useful for the production of bioenergy (Bisaria and Ghose, 1981; Schallmey et al , 2004). In general, the degradation of cellulose occurs by the induction of three types of enzymes: endo-1,4-β-D-glucanase (endocellulase), exo-1,4-β-D-glucanase (exocellulase) and β-glucosidase (cellubiose hydrolase) (Eveleigh, 1981; Hamada et al , 1999). Enzymes called endoglucanases or endocellulases represent a group of cellulases active in the cleavage of random regions within cellulose, producing oligosaccha-rides with variable sizes.…”
Section: Introductionmentioning
confidence: 99%
“…and homologous with P chrysosporium and A bisporus keep similarity of 74% (Chow et al, 1994). Hamada et al (1999) manifested 79% similarity of amino acid catalytic domain comparison cel3 gene with cel2 gene of Irpex lacteus. Truncated cel3 gene in E. coli having only C-terminal region of endoglucanase is able to retain catalytic activity of carboxymethyl cellulose as amino acid sequence are conserved in C-terminal domain of cel3 gene (Jiang et al, 2010).…”
Section: Structure Of Cel3mentioning
confidence: 92%
“…Yagüe et al (1996) also isolated and characterized cellulase gene cel1 and cel2 gene of Irpex lacteus to study regulation of gene sequence where it was found to encode exo-type cellulase, Ex1 and Ex-2. Hamada et al (1999) concluded cellulase genes of Irpex lacteus namely, cel1, cel2 and cel3 were highly similar in their tripartite structure but Hamada et al (1999) mentioned that the cel3 fragment didn't hybridize with cel1 and cel2 whereas Northern hybridization revealed no difference between transcription of cel1, cel2 and cel3 genes in cell of Irpex lacteus. Such gene can be utilized by microorganisms to break primary structure of plant cell wall (Saha et al, 2006).…”
Section: Cel3 Gene In Microorganismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The white rot fungus basidomycete Irpex lacteus grows on fallen wood and decomposes it by secreting multiple enzymes including cellulases, hemicellulases and lignin-degrading enzymes with its strain MC-2 being used as a producer of a commercial enzyme preparation called Driselase marketed by Kyowa Hakko, Co., Ltd. [75]. Hamada et al [114,115] 2005) also isolated a cellulase gene cen1 encoding for a GH5 endoglucanase I termed En-1 (a molecular weight of about 52 kDa) in the basidomycete Irpex lacteus with relatively low specific activities (7.76-25.9 µmol D-glucose/mg protein.min) determined with the soluble substrate CMC [116]. While the basidomycete Irpex lacteus GH5 endoglucanase-I En-1 activity in hydrolyzing Avicel was not reported in the study, the researchers did show that En-1 in combination with the exocellulase Ex-1 had dramatic synergistic effects in enhancing the hydrolysis of crystalline cellulose substrates of Avicel and PASC [116].…”
Section: Properties Of Fungal Biomass Degradation Hemi-cellulases and Cellulasesmentioning
confidence: 99%